Lipid droplet–size mapping in human adipose tissue using a clinical 3T system - Weidlich, Dominik; Honecker, Julius; Boehm, Christof; Ruschke, Stefan; Junker, Daniela; Van, Anh T.; Makowski, Marcus R.; Holzapfel, Christina; Claussnitzer, Melina; Hauner, Hans; Karampinos, Dimitrios C. (Magnetic Resonance in Medicine, 2021)
Purpose: To develop a methodology for probing lipid droplet sizes with a clinical system based on a diffusion-weighted stimulated echo–prepared turbo spin-echo sequence and to validate the methodology in water–fat emulsions and show its applicability in ex vivo adipose-tissue samples. Methods: A diffusion-weighted stimulated echo–prepared preparation was combined with a single-shot turbo spin-echo readout for measurements at different b-values and diffusion times. The droplet size was estimated with an analytical expression, and three fitting approaches were compared: magnitude-based spatial averaging with voxel-wise residual minimization, complex-based spatial averaging with voxel-wise residual minimization, and complex-based spatial averaging with neighborhood-regularized residual minimization. Simulations were performed to characterize the fitting residual landscape and the approaches’ noise performance. The applicability was assessed in oil-in-water emulsions in comparison with laser deflection and in ten human white adipose tissue samples in comparison with histology. Results: The fitting residual landscape showed a minimum valley with increasing extent as the droplet size increased. In phantoms, a very good agreement of the mean droplet size was observed between the diffusion-weighted MRI-based and the laser deflection measurements, showing the best performance with complex-based spatial averaging with neighborhood-regularized residual minimization processing (R2/P: 0.971/0.014). In the human adipose-tissue samples, complex-based spatial averaging with neighborhood-regularized residual minimization processing showed a significant correlation (R2/P: 0.531/0.017) compared with histology. Conclusion: The proposed acquisition and parameter-estimation methodology was able to probe restricted diffusion effects in lipid droplets. The methodology was validated using phantoms, and its feasibility in measuring an apparent lipid droplet size was demonstrated ex vivo in white adipose tissue.
CRIS-Team Scopus Importer:2023-03-08
Keywords: adipocyte diameter; adipose tissue microstructure; DW-TSE; fat diffusion; lipid droplet